Preparation method of antibacterial high-strength HDPE (high-density polyethylene) resin
By mixing fly ash float beads and Schiff base dendritic quaternary ammonium salt with HDPE, an antibacterial and high-strength HDPE resin was prepared, which solved the problem of the lack of antibacterial function of the existing HDPE resin and achieved the dual performance improvement of the material.
Patent Information
- Application Number
- CN202510000326.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The existing HDPE resin lacks antibacterial function, which makes the surface of the product susceptible to bacteria and mold infection, which seriously affects health.
By mixing fly ash float beads and Schiff base dendritic quaternary ammonium salt with HDPE, and through ultrasonic dispersion, stirring reaction, extrusion and granulation, an antibacterial and high strength HDPE resin was prepared.
It realizes the excellent antibacterial and mechanical properties of HDPE resin, which can effectively block the disease transmission pathway and improve the strength of the material.
Smart Images

Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of HDPE resins, in particular to a method for preparing an antibacterial high-strength HDPE resin. Background Art
[0002] High-density polyethylene (HDPE) has the characteristics of good toughness, low price and good chemical corrosion resistance. As its application scope in various fields continues to expand, it has become one of the most consumed general-purpose plastics. However, since high-density polyethylene itself does not have antibacterial function, the surface of the product is prone to infection and breeds a large number of bacteria and molds, which seriously endangers people's health. Therefore, the development of high-density polyethylene with antibacterial function is of great practical significance for blocking the transmission route of the disease and eliminating the source of infection.
[0003] Fly ash beads are a substance rich in aluminosilicates, which are low in price, stable in physical and chemical properties, and have a large specific surface area. They are widely used in various fields. Quaternary ammonium salts are an important class of disinfectant active agents, which are prepared by the reaction of tertiary amines and alkylating agents and have excellent bactericidal, antistatic, and emulsifying properties.
[0004] For example, the patent with authorization announcement number CN 111423609 B discloses an intrinsic antistatic release film base film and its application. The invention uses high-density polyethylene and quaternary ammonium salt as raw materials, and the prepared material has good antistatic effect, but does not improve the mechanical properties of the material. Summary of the invention
[0005] The purpose of the present invention is to overcome one or more deficiencies in the prior art and to provide an antibacterial high-strength HDPE resin. The HDPE resin prepared by the method has excellent antibacterial properties and mechanical properties.
[0006] In order to achieve the above object, a technical solution adopted by the present invention is: A method for preparing an antibacterial high-strength HDPE resin, the preparation method is as follows: (1) Dispersing fly ash floating beads in a 10% by mass nitric acid aqueous solution, ultrasonically dispersing for 50-80 minutes, washing with anhydrous ethanol and deionized water respectively, drying, and then adding them to a 90% by mass ethanol aqueous solution, stirring and dispersing, and then adding Schiff base polysilane thereto, controlling the temperature to 70-85°C, stirring and reacting for 5-8 hours, filtering after the reaction, washing with anhydrous ethanol and deionized water, and drying to obtain modified fly ash floating beads; (2) HDPE, modified fly ash beads, and Schiff base dendritic quaternary ammonium salt are added to a high-speed mixer and mixed evenly, and then placed in a twin-screw extruder for extrusion granulation and injection molding to obtain an antibacterial high-strength HDPE resin.
[0007] Preferably, in (1), the mass ratio of fly ash beads to Schiff base polysilane is 1:0.1-0.5.
[0008] Preferably, in (2), the mass ratio of HDPE, modified fly ash floating beads, and Schiff base dendritic quaternary ammonium salt is 100:10-30:2-10.
[0009] Further preferably, in (1), the preparation method of Schiff base polysilane is: A1. Add 5-aminoresorcinol to a flask filled with methanol solvent, then add sodium hydroxide thereto, stir and react for 20-50 min, then add 3,5-dihydroxybenzaldehyde thereto, heat to 60°C, react for 2-4 h, after the reaction is completed, cool to room temperature, distill under reduced pressure, wash and dry to obtain intermediate product 1, use the aldehyde group in 3,5-dihydroxybenzaldehyde and the amino group in 5-aminoresorcinol to react with Schiff base to obtain intermediate product 1, the reaction route is: ; A2. Under a nitrogen atmosphere, the intermediate product 1 and sodium carbonate are added to N,N-dimethylformamide, stirred and dispersed, and then iodopropyltriethoxysilane is added thereto, and the temperature is raised to 70-80°C, and the reaction is carried out for 4-8 hours. After the reaction is completed, the mixture is washed with saturated brine, dried, and rotary evaporated to obtain Schiff base polysilane. The intermediate product 1 is used to carry out a substitution reaction with iodopropyltriethoxysilane to obtain Schiff base polysilane. The reaction route is: .
[0010] More preferably, in A1, the molar ratio of 5-aminoresorcinol, sodium hydroxide and 3,5-dihydroxybenzaldehyde is 1:1-1.2:1-1.5.
[0011] Further preferably, in A2, the molar ratio of the intermediate product 1, sodium carbonate and iodopropyltriethoxysilane is 1:5-6:10-14.
[0012] Preferably, in (2), the preparation method of the Schiff base dendritic quaternary ammonium salt is: S1. Add intermediate product 1 and epichlorohydrin into a flask, and then add tetrabutylammonium bromide thereto, wherein the molar ratio of intermediate product 1, epichlorohydrin and tetrabutylammonium bromide is 1:20-25:0.07-0.1, heat to 100-110°C, react for 5-8h, then add 40% sodium hydroxide aqueous solution thereto, react for 2-3h, after the reaction is completed, add deionized water for washing, let stand, distill under reduced pressure, and dry to obtain intermediate product 2, and use intermediate product 1 to carry out substitution reaction with epichlorohydrin to obtain intermediate product 2, and the reaction route is: ; S2, adding an alkyl tertiary amine to deionized water, stirring and dispersing, then adding 36% hydrochloric acid thereto, controlling the temperature to 40-60°C, acidifying for 10-15min, then adding intermediate product 2 thereto, controlling the temperature to 80-100°C, reacting for 6-10h, after the reaction is completed, washing with deionized water, drying, to obtain a Schiff base dendritic quaternary ammonium salt, using an alkyl tertiary amine and the epoxy group in the intermediate product 2 to carry out a quaternization reaction, to obtain a Schiff base dendritic quaternary ammonium salt, the reaction route is: , where n is any value among 11, 13, 15, and 17.
[0013] Further preferably, in S2, the molar ratio of the alkyl tertiary amine to the intermediate product 2 is 4.2-5:1.
[0014] Further preferably, in S2, the alkyl tertiary amine is one of N,N-dimethyldodecyl tertiary amine, N,N-dimethyltetradecyl tertiary amine, N,N-dimethylhexadecanyl tertiary amine and N,N-dimethyloctadecyl tertiary amine.
[0015] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: The Schiff base dendritic quaternary ammonium salt prepared by the present invention contains a branched long-chain structure, which can be dispersed in the matrix resin by adding it to high-density polyethylene, forming more cross-linked network structures, generating more cross-linking sites, and when subjected to external force, the external force can be dispersed into other side chains through the cross-linking sites, thereby improving the mechanical properties of the resin material. In addition, the fly ash floating beads contained therein can be uniformly dispersed in the matrix resin after organic treatment, and as stress concentration points, under the action of external stress, they absorb stress energy, generate a large number of holes and microcracks around the particles, better promote the matrix resin to yield and plastic deformation, and further improve the mechanical properties of the matrix resin.
[0016] The Schiff base dendritic quaternary ammonium salt and modified fly ash floating beads prepared by the present invention contain Schiff base structure and quaternary ammonium salt structure, both of which have antibacterial effects. When added to the matrix resin, they can mutually assist in improving the antibacterial effect of the matrix resin. The HDPE resin prepared by the present invention has been proven to have relatively excellent antibacterial effects and mechanical properties through experiments. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0018] Preparation method of iodopropyltriethoxysilane: Under a nitrogen atmosphere, add 20g of chloropropyltriethoxysilane to an acetone solvent, stir and disperse, then add 18.4g of potassium iodide, heat and reflux for 48h, after the reaction is completed, cool, filter, and rotary evaporate to obtain iodopropyltriethoxysilane.
[0019] Example 1 (1) Add 0.4 mol of 5-aminoresorcinol into a flask containing methanol solvent, add 0.4 mol of sodium hydroxide, stir and react for 40 min, then add 0.5 mol of 3,5-dihydroxybenzaldehyde, heat to 60°C, react for 4 h. After the reaction is completed, cool to room temperature, evaporate under reduced pressure, wash and dry to obtain intermediate 1.
[0020] (2) 0.1 mol of the intermediate product 1 and 2 mol of epichlorohydrin were added to a flask, and then 9 mmol of tetrabutylammonium bromide was added thereto. The temperature was raised to 105°C and the reaction was carried out for 7 hours. Then, a 40% aqueous sodium hydroxide solution was added thereto and the reaction was carried out for 3 hours. After the reaction was completed, deionized water was added for washing, the mixture was allowed to stand, and vacuum distillation and drying were performed to obtain the intermediate product 2.
[0021] (3) Add 0.45 mol of N,N-dimethyltetradecamine to deionized water, stir and disperse, then add 36% hydrochloric acid, control the temperature at 50°C, acidify for 12 min, then add 0.1 mol of intermediate 2, control the temperature at 90°C, react for 8 h, after the reaction is completed, wash with deionized water, and dry to obtain Schiff base dendritic quaternary ammonium salt.
[0022] (4) Under a nitrogen atmosphere, 0.1 mol of the intermediate product 1 and 0.5 mol of sodium carbonate were added to N,N-dimethylformamide and stirred for dispersion. Then, 1.4 mol of iodopropyltriethoxysilane was added thereto. The temperature was raised to 70°C and the reaction was carried out for 8 h. After the reaction was completed, the mixture was washed with saturated brine, dried, and rotary evaporated to obtain Schiff base polysilane.
[0023] (5) Disperse 20 g of fly ash beads in a 10% by mass nitric acid aqueous solution, ultrasonically disperse for 80 min, wash with anhydrous ethanol and deionized water respectively, dry, add them to a 90% by mass ethanol aqueous solution, stir and disperse, add 2 g of Schiff base polysilane, control the temperature to 80 °C, stir and react for 8 h, filter after the reaction, wash with anhydrous ethanol and deionized water, and dry to obtain modified fly ash beads.
[0024] (6) Add 100 g of HDPE, 10 g of modified fly ash beads, and 2 g of Schiff base dendritic quaternary ammonium salt into a high-speed mixer and mix evenly. Then place the mixture in a twin-screw extruder for extrusion granulation. The five-zone temperatures are controlled at 190°C, 200°C, 220°C, 220°C, and 200°C. The screw speed is 120 r / min. The mixture is injection molded at 200°C to obtain an antibacterial high-strength HDPE resin.
[0025] Example 2 (1) 0.4 mol of 5-aminoresorcinol was added to a flask containing methanol solvent, and 0.48 mol of sodium hydroxide was added thereto. The mixture was stirred for reaction for 20 min, and then 0.6 mol of 3,5-dihydroxybenzaldehyde was added thereto. The temperature was raised to 60°C and the reaction was carried out for 2 h. After the reaction was completed, the mixture was cooled to room temperature, distilled under reduced pressure, washed and dried to obtain intermediate 1.
[0026] (2) 0.1 mol of intermediate product 1 and 2.5 mol of epichlorohydrin were added to a flask, and then 10 mmol of tetrabutylammonium bromide was added thereto. The temperature was raised to 110°C and the reaction was carried out for 5 h. Then, a 40% aqueous sodium hydroxide solution was added thereto and the reaction was carried out for 3 h. After the reaction was completed, deionized water was added for washing, the mixture was allowed to stand, and vacuum distillation and drying were performed to obtain intermediate product 2.
[0027] (3) Add 0.5 mol of N,N-dimethyldodecylamine to deionized water, stir and disperse, then add 36% hydrochloric acid, control the temperature to 40°C, acidify for 10 min, then add 0.1 mol of intermediate 2, control the temperature to 90°C, react for 10 h. After the reaction is completed, wash with deionized water and dry to obtain Schiff base dendritic quaternary ammonium salt.
[0028] (4) Under a nitrogen atmosphere, 0.1 mol of the intermediate product 1 and 0.55 mol of sodium carbonate were added to N,N-dimethylformamide and stirred for dispersion. Then, 1 mol of iodopropyltriethoxysilane was added thereto. The temperature was raised to 75°C and the reaction was carried out for 4 h. After the reaction was completed, the mixture was washed with saturated brine, dried, and rotary evaporated to obtain Schiff base polysilane.
[0029] (5) Disperse 20 g of fly ash beads in a 10% by mass nitric acid aqueous solution, ultrasonically disperse for 80 min, wash with anhydrous ethanol and deionized water respectively, dry, add them to a 90% by mass ethanol aqueous solution, stir and disperse, add 4 g of Schiff base polysilane, control the temperature to 80 °C, stir and react for 8 h, filter after the reaction, wash with anhydrous ethanol and deionized water, and dry to obtain modified fly ash beads.
[0030] (6) Add 100 g of HDPE, 15 g of modified fly ash beads, and 4 g of Schiff base dendritic quaternary ammonium salt into a high-speed mixer and mix evenly. Then place the mixture in a twin-screw extruder for extrusion granulation. The temperatures in the five zones are controlled at 190°C, 200°C, 220°C, 220°C, and 200°C. The screw speed is 120 r / min. The mixture is injection molded at 200°C to obtain an antibacterial high-strength HDPE resin.
[0031] Example 3 (1) 0.4 mol of 5-aminoresorcinol was added to a flask containing methanol solvent, and 0.45 mol of sodium hydroxide was added thereto. The mixture was stirred for reaction for 50 min, and then 0.4 mol of 3,5-dihydroxybenzaldehyde was added thereto. The temperature was raised to 60°C and the reaction was carried out for 3 h. After the reaction was completed, the mixture was cooled to room temperature, distilled under reduced pressure, washed and dried to obtain intermediate 1.
[0032] (2) 0.1 mol of intermediate product 1 and 2.5 mol of epichlorohydrin were added to a flask, and then 7 mmol of tetrabutylammonium bromide was added thereto. The temperature was raised to 105°C and the reaction was carried out for 8 h. Then, a 40% aqueous sodium hydroxide solution was added thereto and the reaction was carried out for 2 h. After the reaction was completed, deionized water was added for washing, the mixture was allowed to stand, and vacuum distillation and drying were performed to obtain intermediate product 2.
[0033] (3) Add 0.45 mol of N,N-dimethylhexadecylamine to deionized water, stir and disperse, then add 36% hydrochloric acid, control the temperature at 60°C, acidify for 10 min, then add 0.1 mol of intermediate 2, control the temperature at 80°C, react for 6 h. After the reaction is completed, wash with deionized water and dry to obtain Schiff base dendritic quaternary ammonium salt.
[0034] (4) Under a nitrogen atmosphere, 0.1 mol of the intermediate product 1 and 0.6 mol of sodium carbonate were added to N,N-dimethylformamide and stirred for dispersion. Then, 1.2 mol of iodopropyltriethoxysilane was added thereto. The temperature was raised to 80°C and the reaction was carried out for 6 h. After the reaction was completed, the mixture was washed with saturated brine, dried, and rotary evaporated to obtain Schiff base polysilane.
[0035] (5) Disperse 20 g of fly ash beads in a 10% by mass nitric acid aqueous solution, ultrasonically disperse for 60 min, wash with anhydrous ethanol and deionized water respectively, dry, add them to a 90% by mass ethanol aqueous solution, stir and disperse, add 6 g of Schiff base polysilane, control the temperature to 75 °C, stir and react for 5 h, filter after the reaction, wash with anhydrous ethanol and deionized water, and dry to obtain modified fly ash beads.
[0036] (6) Add 100 g of HDPE, 20 g of modified fly ash beads, and 6 g of Schiff base dendritic quaternary ammonium salt into a high-speed mixer and mix evenly. Then place the mixture in a twin-screw extruder for extrusion granulation. The temperatures in the five zones are controlled at 190°C, 200°C, 220°C, 220°C, and 200°C. The screw speed is 120 r / min. The mixture is injection molded at 200°C to obtain an antibacterial high-strength HDPE resin.
[0037] Example 4 (1) Add 0.4 mol of 5-aminoresorcinol into a flask containing methanol solvent, add 0.4 mol of sodium hydroxide, stir and react for 40 min, then add 0.6 mol of 3,5-dihydroxybenzaldehyde, heat to 60°C, react for 3 h. After the reaction is completed, cool to room temperature, evaporate under reduced pressure, wash and dry to obtain intermediate 1.
[0038] (2) 0.1 mol of intermediate product 1 and 2 mol of epichlorohydrin were added to a flask, and then 10 mmol of tetrabutylammonium bromide was added thereto. The temperature was raised to 100°C and the reaction was carried out for 6 hours. Then, a 40% aqueous sodium hydroxide solution was added thereto and the reaction was carried out for 3 hours. After the reaction was completed, deionized water was added for washing, the mixture was allowed to stand, and vacuum distillation and drying were performed to obtain intermediate product 2.
[0039] (3) Add 0.5 mol of N,N-dimethylhexadecylamine to deionized water, stir and disperse, then add 36% hydrochloric acid, control the temperature at 40°C, acidify for 15 min, then add 0.1 mol of intermediate 2, control the temperature at 90°C, react for 10 h, after the reaction is completed, wash with deionized water, and dry to obtain Schiff base dendritic quaternary ammonium salt.
[0040] (4) Under a nitrogen atmosphere, 0.1 mol of the intermediate product 1 and 0.55 mol of sodium carbonate were added to N,N-dimethylformamide and stirred for dispersion. Then, 1.2 mol of iodopropyltriethoxysilane was added thereto. The temperature was raised to 75°C and the reaction was carried out for 8 h. After the reaction was completed, the mixture was washed with saturated brine, dried, and rotary evaporated to obtain Schiff base polysilane.
[0041] (5) Disperse 20 g of fly ash beads in a 10% by mass nitric acid aqueous solution, ultrasonically disperse for 50 min, wash with anhydrous ethanol and deionized water respectively, dry, add them to a 90% by mass ethanol aqueous solution, stir and disperse, add 8 g of Schiff base polysilane, control the temperature to 85 °C, stir and react for 8 h, filter after the reaction, wash with anhydrous ethanol and deionized water, and dry to obtain modified fly ash beads.
[0042] (6) Add 100 g of HDPE, 25 g of modified fly ash beads, and 8 g of Schiff base dendritic quaternary ammonium salt into a high-speed mixer and mix evenly. Then place the mixture in a twin-screw extruder for extrusion granulation. The temperatures in the five zones are controlled at 190°C, 200°C, 220°C, 220°C, and 200°C. The screw speed is 120 r / min. The mixture is injection molded at 200°C to obtain an antibacterial high-strength HDPE resin.
[0043] Example 5 (1) 0.4 mol of 5-aminoresorcinol was added to a flask containing methanol solvent, and 0.45 mol of sodium hydroxide was added thereto. The mixture was stirred for reaction for 40 min, and then 0.6 mol of 3,5-dihydroxybenzaldehyde was added thereto. The temperature was raised to 60°C and the reaction was carried out for 4 h. After the reaction was completed, the mixture was cooled to room temperature, distilled under reduced pressure, washed and dried to obtain intermediate 1.
[0044] (2) 0.1 mol of intermediate product 1 and 2 mol of epichlorohydrin were added to a flask, and then 8 mmol of tetrabutylammonium bromide was added thereto. The temperature was raised to 100°C and the reaction was carried out for 5 hours. Then, a 40% aqueous sodium hydroxide solution was added thereto and the reaction was carried out for 2 hours. After the reaction was completed, deionized water was added for washing, the mixture was allowed to stand, and vacuum distillation and drying were performed to obtain intermediate product 2.
[0045] (3) Add 0.42 mol of N,N-dimethyloctadecylamine to deionized water, stir and disperse, then add 36% hydrochloric acid, control the temperature to 45°C, acidify for 15 minutes, then add 0.1 mol of intermediate 2, control the temperature to 100°C, react for 8 hours, after the reaction is completed, wash with deionized water, and dry to obtain Schiff base dendritic quaternary ammonium salt.
[0046] (4) Under a nitrogen atmosphere, 0.1 mol of the intermediate product 1 and 0.55 mol of sodium carbonate were added to N,N-dimethylformamide and stirred for dispersion. Then, 1.4 mol of iodopropyltriethoxysilane was added thereto. The temperature was raised to 75°C and the reaction was carried out for 8 h. After the reaction was completed, the mixture was washed with saturated brine, dried, and rotary evaporated to obtain Schiff base polysilane.
[0047] (5) Disperse 20 g of fly ash beads in a 10% by mass nitric acid aqueous solution, ultrasonically disperse for 80 min, wash with anhydrous ethanol and deionized water respectively, dry, add them to a 90% by mass ethanol aqueous solution, stir and disperse, add 10 g of Schiff base polysilane, control the temperature to 70 ° C, stir and react for 6 h, filter after the reaction, wash with anhydrous ethanol and deionized water, and dry to obtain modified fly ash beads.
[0048] (6) Add 100 g of HDPE, 30 g of modified fly ash beads, and 10 g of Schiff base dendritic quaternary ammonium salt into a high-speed mixer and mix evenly. Then place the mixture in a twin-screw extruder for extrusion granulation. The temperatures in the five zones are controlled at 190°C, 200°C, 220°C, 220°C, and 200°C. The screw speed is 120 r / min. The mixture is injection molded at 200°C to obtain an antibacterial high-strength HDPE resin.
[0049] Comparative Example 1 The difference between this comparative example and Example 1 is that fly ash floating beads are used in step (6) instead of modified fly ash floating beads.
[0050] Comparative Example 2 The difference between this comparative example and Example 1 is that step (6) does not contain Schiff base dendritic quaternary ammonium salt.
[0051] Use an Izod impact tester to test the impact strength of the resin material; The tensile strength of the resin material was tested using a universal testing material machine.
[0052] Table 1: Impact strength / J·m-1 Tensile strength / MPa Example 1 89.1 32.9 Example 2 93.4 35.6 Example 3 98.0 39.8 Example 4 102.4 42.0 Example 5 97.3 40.1 Comparative Example 1 85.2 29.0 Comparative Example 2 82.4 26.3 As can be seen from the table, the HDPE resin prepared by the present invention has good strength. From the data of Comparative Example 1 and Example 1, it can be seen that the fly ash floating beads treated with organic materials have good compatibility with the resin of the matrix, good dispersion, and higher strength. From Comparative Example 2 and Example 1, it can be seen that since the Schiff base dendritic quaternary ammonium salt contains more long chain structures, it is dispersed in the matrix resin and can produce more cross-linking sites, so its mechanical properties are better.
[0053] The antibacterial properties of resin materials were tested according to GB / T 31402-2015, and the test bacteria were Escherichia coli.
[0054] Table 2: Antibacterial rate / % Example 1 80.3 Example 2 86.2 Example 3 95.5 Example 4 99.9 Example 5 99.9 Comparative Example 2 65.4 It can be seen from the table that the quaternary ammonium salt structure and the Schiff base structure have a better synergistic antibacterial effect, and with the increase in dosage, the antibacterial rate can reach up to 99.9%.
[0055] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those familiar with the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and modifications made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing an antibacterial high-strength HDPE resin, characterized in that: The preparation method is as follows: (1) Dispersing fly ash floating beads in a 10% by mass nitric acid aqueous solution, ultrasonically dispersing for 50-80 minutes, washing with anhydrous ethanol and deionized water respectively, drying, and then adding them to a 90% by mass ethanol aqueous solution, stirring and dispersing, adding Schiff base polysilane thereto, controlling the temperature to 70-85°C, stirring and reacting for 5-8 hours, filtering after the reaction, washing with anhydrous ethanol and deionized water, and drying to obtain modified fly ash floating beads; (2) HDPE, modified fly ash beads, and Schiff base dendritic quaternary ammonium salt are added to a high-speed mixer and mixed evenly, and then placed in a twin-screw extruder for extrusion granulation and injection molding to obtain an antibacterial high-strength HDPE resin.
2. The method for preparing the antibacterial high-strength HDPE resin according to claim 1, characterized in that: In the above (1), the mass ratio of fly ash beads to Schiff base polysilane is 1:0.1-0.
5.
3. The method for preparing the antibacterial high-strength HDPE resin according to claim 1, characterized in that: In the above (2), the mass ratio of HDPE, modified fly ash floating beads and Schiff base dendritic quaternary ammonium salt is 100:10-30:2-10.
4. The method for preparing the antibacterial high-strength HDPE resin according to claim 1, characterized in that: In (1), the preparation method of Schiff base polysilane is: A1. Add 5-aminoresorcinol to a flask containing methanol solvent, then add sodium hydroxide, stir and react for 20-50 minutes, then add 3,5-dihydroxybenzaldehyde, heat to 60°C, react for 2-4 hours, and after the reaction is completed, cool to room temperature, distill under reduced pressure, wash and dry to obtain intermediate 1; A2. Under a nitrogen atmosphere, add the intermediate product 1 and sodium carbonate to N,N-dimethylformamide, stir and disperse, then add iodopropyltriethoxysilane, raise the temperature to 70-80°C, react for 4-8h, and after the reaction, wash with saturated brine, dry, and rotary evaporate to obtain Schiff base polysilane.
5. The method for preparing the antibacterial high-strength HDPE resin according to claim 4, characterized in that: In the A1, the molar ratio of 5-aminoresorcinol, sodium hydroxide and 3,5-dihydroxybenzaldehyde is 1:1-1.2:1-1.
5.
6. The method for preparing the antibacterial high-strength HDPE resin according to claim 4, characterized in that: In A2, the molar ratio of the intermediate product 1, sodium carbonate and iodopropyltriethoxysilane is 1:5-6:10-14.
7. The method for preparing the antibacterial high-strength HDPE resin according to claim 1, characterized in that: In (2), the preparation method of the Schiff base dendritic quaternary ammonium salt is: S1, adding intermediate product 1 and epichlorohydrin into a flask, and then adding tetrabutylammonium bromide thereto, wherein the molar ratio of the intermediate product 1, epichlorohydrin and tetrabutylammonium bromide is 1:20-25:0.07-0.1, heating to 100-110°C, reacting for 5-8h, and then adding a 40% sodium hydroxide aqueous solution thereto, reacting for 2-3h, after the reaction is completed, adding deionized water for washing, standing, distilling under reduced pressure, and drying to obtain intermediate product 2; S2. Add alkyl tertiary amine to deionized water, stir and disperse, then add 36% hydrochloric acid, control the temperature to 40-60°C, acidify for 10-15 minutes, then add intermediate 2, control the temperature to 80-100°C, react for 6-10 hours, after the reaction is completed, wash with deionized water, and dry to obtain Schiff base dendritic quaternary ammonium salt.
8. The method for preparing the antibacterial high-strength HDPE resin according to claim 7, characterized in that: In S2, the molar ratio of the alkyl tertiary amine to the intermediate product 2 is 4.2-5:
1.
9. The method for preparing the antibacterial high-strength HDPE resin according to claim 7, characterized in that: In S2, the alkyl tertiary amine is one of N,N-dimethyl dodecanedrine, N,N-dimethyltetradecamine, N,N-dimethylhexadecaneamine and N,N-dimethyloctadecaneamine.
Citation Information
Patent Citations
An Intrinsic Antistatic Release Film Base Film and Its Application
CN111423609B
Preparation method of micro-capsule fly ash floating bead toughened and reinforced phenolic foam
CN104086946A
High-temperature-resistant prepreg for producing carbon fiber composite material, and preparation method therefor
WO2024124837A1
Cited By
Preparation method of flame-retardant antibacterial PE pipe
CN121045662A